2014
DOI: 10.1007/s00792-014-0679-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour and tolerance to ionic liquid [emim]OAc in GH10 xylanase from Thermoascus aurantiacus SL16W

Abstract: GH10 xylanase from Thermoascus aurantiacus strain SL16W (TasXyn10A) showed high stability and activity up to 70-75 °C. The enzyme's half-lives were 101 h, 65 h, 63 min and 6 min at 60, 70, 75 and 80 °C, respectively. The melting point (T m), as measured by DSC, was 78.5 °C, which is in line with a strong activity decrease at 75-80 °C. The biomass-dissolving ionic liquid 1-ethyl-3-methylimidazolium acetate ([emim]OAc) in 30 % concentration had a small effect on the stability of TasXyn10A; T m decreased by only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 42 publications
1
49
0
Order By: Relevance
“…In previous studies and in this study, family GH10 xylanases were generally found to be more IL‐tolerant compared with family GH11 enzymes . Earlier findings with [EMIM]AcO suggest that the IL interferes with substrate binding in the active site and this competitive inhibition may be more pronounced with family GH11 xylanases .…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…In previous studies and in this study, family GH10 xylanases were generally found to be more IL‐tolerant compared with family GH11 enzymes . Earlier findings with [EMIM]AcO suggest that the IL interferes with substrate binding in the active site and this competitive inhibition may be more pronounced with family GH11 xylanases .…”
Section: Resultssupporting
confidence: 62%
“…Earlier findings with [EMIM]AcO suggest that the IL interferes with substrate binding in the active site and this competitive inhibition may be more pronounced with family GH11 xylanases . The difference in activity among these enzymes in the presence of ILs appears to be based on differences in the active site and was revealed by molecular docking studies between the enzyme and the IL cation . Probably the narrow and deep active site of GH11 xylanases allows transient binding of large amounts of [EMIM] + cations, thus preventing the binding of a substrate.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations